Thrombelastographic changes and early rebleeding in cirrhotic patients with variceal bleeding. Issue 2 (1st August 1998) - Chau, T N; Chan, Y W; Patch, D; Tokunaga, S; Greenslade, L; Burroughs, A K
Abstract : Background —Routine coagulation tests do not necessarily reflect haemostasis in vivo in cirrhotic patients, particularly those who have bleeding varices. Thrombelastography (TEG) can provide a global assessment of haemostatic function from initial clot formation to clot dissolution. Aim —To evaluate TEG changes in cirrhotic patients with variceal bleeding and their association with early rebleeding. Patients/Methods —Twenty cirrhotic patients with active variceal bleeding had serial TEG and routine coagulation tests daily for seven days. The TEG variables before the day of rebleeding (n = 6) were compared with those of patients without rebleeding (n = 14). Results —Baseline characteristics of the rebleeding and non-rebleeding groups were comparable apart from a higher incidence of uncontrolled infection on the day of rebleeding in the rebleeding group (p = 0.007). The patients in the rebleeding group were more hypocoagulable before the day of rebleeding as shown by longer r (42 v 24 mm, p<0.001) and k (48 v 13 mm, p<0.001) and smaller a (12 v 38°, p<0.001) compared with the mean of daily results of the non-rebleeding group. Routine coagulation tests, however, showed no significant differences between the two groups. Conclusion —The results of serial TEG measurements suggest that hypocoagulability may be associated with early rebleeding in cirrhotic patients.